Maintaining Norms about Expressed Emotions: The Case of Bill Collectors - Sutton, Robert I. (Administrative Science Quarterly, 1991)
I wish to thank Max Bazerman, Kimberly Elsbach, Connie Gersick, Roderick Kramer, Keith Murnighan, Marina Park, Lorna Peden, Jeffrey Pfeffer, Linda Pike, Anat Rafaeli, John Van Maanen, and three anonymous ASO reviewers for their contributions to this article. I especially wish to thank Gerald Salancik for urging me to narrow and focus my arguments in ways that improved this article considerably. A qualitative study of a bill-collection organization was used to identify norms about the emotions that collectors are expected to convey to debtors and the means used by the organization to maintain such norms given that collectors' expressed emotions are simultaneously influenced by their inner feelings. These data indicate that collectors are selected, socialized, and rewarded for following the general norm of conveying urgency (high arousal with a hint of irritation) to debtors. Collectors are further socialized and rewarded to adjust their expressed emotions in response to variations in debtor demeanor. These contingent norms sometimes clash with collectors' feelings toward debtors. Bill collectors are taught to cope with such emotive dissonance by using cognitive appraisals that help them become emotionally detached from debtors and by releasing unpleasant feelings without communicating these emotions to debtors. The discussion focuses on the implications of this research for developing general theory about the expression of emotion in organizational life.'